An Overview of Indonesia’s Maritime Strategy - buddy suseto; Zarina Othman; Farizal Bin Mohd Razalli (Indonesian Journal of Geography, 2018)
As one of the consent maritime on earth, Indonesia has no maritime strategy. Maritime strategy is important not only to protect state’s maritime pathway, but also as part of a national strategy. This article is designed to provide an understanding way for the Indonesian readers to urgently prepare and design a maritime strategy. It is argued that a maritime strategy for Indonesia is needed because of the changing landscape of the international threat such maritime security nontraditional issues. It affects the international trade through the Malacca Strait, Sunda Strait, and Lombok Strait. Data for the articles have been collected from secondary reliable sources. The Early finding of the study suggests that Indonesia needs to shape a maritime strategy to reduce threats at sea and guarantee the security most importantly in the archipelagic sea-lanes (ASL) as an international route. In conclusion, a brief overview of the study indicates that Indonesia urgency needs to establish a maritime strategy.